Analisa Penerapan Whistleblowing System pada PT TASPEN - Fauziyah, Zahra Putri; Prabawani, Bulan; Dewi, Reni Shinta (Universitas Diponegoro, 2021)
Abstract: Fraud in insurance companies has become a rife thing lately. The Association Certified Fraud ExaminersI (ACFE) noted that in 2019 there were 239 cases of fraud in which the companies that suffered the most losses were financial sector companies in which the insurance company was included. One way to implement a clean and professional work environment is to implement Good Corporate Governance. To support this, it is necessary to optimize the application of the whistleblowing system as an element of Good Corporate Governance as a control and prevention of fraud. In this study, the author aims to determine how the implementation of the whistleblowing system at PT TASPEN. The author uses a qualitative method with a qualitative descriptive approach and gives results that in the implementation of the whistleblowing system PT TASPEN has almost applied all the indicators formulated in the Whistleblowing System by the National Committee on Governance, except for the hard skills training for employees and benchmarking activities.Keywords : Whistleblowing System; Fraud;GCGAbstrak: Kecurangan dalam perusahaan asuransi menjadi hal yang marak terjadi akhir-akhir ini. Association Certified Fraud ExaminersI (ACFE) mencatat bahwa dalam tahun 2019 terdapat 239 kasus fraud dimana perusahaan yang paling dirugikan adalah perusahaan sektor keuangan yang mana perusahaan asuransi masuk didalamnya. Salah satu cara menerapkan lingkungan kerja yang bersih dan profesional adalah dengan mengimplementasikan Good Corporate Governance. Untuk mendukung hal tersebut perlu dioptimalkan penerapan whistleblowing system sebagai salah satu elemen Good Corporate Governance sebagai pengendalian dan pencegahan adanya kecurangan. Pada penelitian ini penulis bertujuan untuk mengertahui bagaimana pelaksanaan whistleblowing system pada PT TASPEN. Penulis menggunakan metode kualitatif dengan pendekataan deskriptif kualitatif dan memberikan hasil bahwa dalam pelaksanaan whistleblowing system PT TASPEN hampir sudah menerapkan semua indikator yang dirumuskan dalam Pedoman Pelaporan Pelanggaran - Whistleblowing System oleh Komite Nasional Kebijakan Governance terkecuali bagian pelatihan hardskill kepada karyawan dan kegiatan benchmarking.Kata Kunci : Whistleblowing System; Fraud; GCGÂ